Mutations in MYT1, encoding the myelin transcription factor 1, are a rare cause of OAVS. Issue 11 (29th June 2016) - Lopez, Estelle; Berenguer, Marie; Tingaud-Sequeira, Angèle; Marlin, Sandrine; Toutain, Annick; Denoyelle, Françoise; Picard, Arnaud; Charron, Sabine; Mathieu, Guilaine; de Belvalet, Harmony; Arveiler, Benoit; Babin, Patrick J; et al.
Abstract : Background: Oculo-auriculo-vertebral spectrum (OAVS) is a developmental disorder involving first and second branchial arches derivatives, mainly characterised by asymmetric ear anomalies, hemifacial microsomia, ocular defects and vertebral malformations. Although numerous chromosomal abnormalities have been associated with OAVS, no causative gene has been identified so far. Objectives: We aimed to identify the first causative gene for OAVS. Methods: As sporadic cases are mostly described in Goldenhar syndrome, we have performed whole exome sequencing (WES) on selected affected individuals and their unaffected parents, looking for de novo mutations. Candidate gene was tested through transient knockdown experiment in zebrafish using a morpholino-based approach. A functional test was developed in cell culture in order to assess deleterious consequences of mutations. Results: By WES, we identified a heterozygous nonsense mutation in one patient in the myelin transcription factor 1 ( MYT1 ) gene. Further, we detected one heterozygous missense mutation in another patient among a cohort of 169 patients with OAVS. This gene encodes the MYT1 . Functional studies by transient knockdown of myt1a, homologue of MYT1 in zebrafish, led to specific craniofacial cartilage alterations. Treatment with all-trans retinoic acid (RA), a known teratogenic agent causing OAVS, led to an upregulation of cellular endogenous MYT1 expression. Additionally, cellular wild-type MYT1 overexpression induced a downregulation of RA receptor β ( RARB), whereas mutated MYT1 did not. Conclusion: We report MYT1 as the first gene implicated in OAVS, within the RA signalling pathway.